Empowering Leadership dalam Membentuk Employee Creativity - Tri Siwi Agustina; Adi Bintang Pradana (Jurnal Bisnis dan Manajemen (JBM), 2021)
The purpose of this study is to analyze how the influence of a leader's attitude in delegating authority to his subordinates (empowering leadership). Empowering leadership have an impact on the ability of employees to generate new and useful ideas for the organization (employee creativity). This study also analyzes how individual beliefs in producing something creative (creative self-efficacy) as a mediating variable. Employee trust in superiors (trust in supervisors) and uncertain and threatening situations (uncertainty avoidance) are moderating variables. TThis study uses primary data from 51 lecturers where the data is obtained using a questionnaire distributed to lecturers at the Faculty of Nursing, University of Muhammadiyah Jakarta. This study uses statistical tools Partial Least Square (SmartPLS 3.0). Based on the research results, it shows that creative self-efficacy fully mediates the relationship between empowering leadership and employee creativity. Keywords : Empowering Leadership, Employee Creativity, Creative Self-Efficacy, Trust in Supervisor, Uncertainty Avoidance ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh sikap pemimpin dalam pendelegasian wewenang pada dosen fakultas ilmu keperawatan dalam menghasilkan ide-ide baru dan berguna untuk organisasi (employee creativity). Penelitian ini juga menganalisis keyakinan individu dalam menghasilkan sesuatu yang kreatif (creative self-efficacy) sebagai variabel mediasi. Kepercayaan karyawan kepada atasan (trust in supervisor) dan situasi yang tidak pasti dan bersifat mengancam (uncertainty avoidance) sebagai variabel moderasi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Penelitian ini menggunakan data primer dari 51 dosen Fakultas Ilmu Keperawatan Universitas Muhammadiyah Jakarta. Untuk menguji hipotesis, digunakan alat bantu statistik Partial Least Square (SmartPLS 3.0). Berdasarkan hasil penelitian creative self-efficacy memediasi secara penuh hubungan empowering leadership dan employee creativity. Kata Kunci : Empowering Leadership, Employee Creativity, Creative Self-Efficacy, Trust in Supervisor, Uncertainty Avoidance